IMPLEMENTASI HUKUM ADAT DALAM PEMAKSAAN PERNIKAHAN ANAK DI BAWAH UMUR PERSPEKTIF (UNDANG-UNDANG NO. 1 TAHUN 1974 DAN KHI) - Abdul Aziz Harahap; Rahmad Fahriansyah Pasaribu; Laila Kalsum Hasibuan; Nasruddin Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2023)
The ability of an individual to make decisions is measured by their maturity, especially when it comes to marriage. However, marriages often occur when someone is below the age of maturity. We can also find cases of child marriages, which result in burdening the child with responsibilities they are not yet capable of handling. This research is a normative legal study that aims to answer how the Religious Court should make policies regarding children, particularly in the context of marriage, considering the potential consequences after the dispensation of marriage is granted The research finds that granting dispensation for child marriages has negative impacts on the sustainability of a happy household based on the belief in the Almighty God. The dispensation of child marriages granted by the court upon the request of the parents, usually due to incidents of pregnancy, adds pressure to the child and fails to create the expected happiness as envisioned by the Marriage Law of 1974 and the Compilation of Islamic Law (KHI). Although the Marriage Law allows such marriages based on the parents' request and does not violate religious beliefs and practices, this research highlights the adverse effects of granting such dispensations.